2012
DOI: 10.3892/ol.2012.872
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of lung-specific toxicity induced by epidermal growth factor receptor tyrosine kinase inhibitors

Abstract: Abstract. Lung-specific toxicity induced by epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) for the treatment of non-small cell lung cancer (NSCLC) has emerged as a critical side-effect. Although the clinical features of the pulmonary side-effects of TKIs have been characterized, the details of the molecular mechanisms in the development of this lung-specific toxicity remain to be elucidated. EGFR-dependent epithelial regeneration and restoration plays an important role in the recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Such signal fades away after normal organogenesis and tissue injury/repair to maintain homeostasis [ 37 ]. Unlike honokiol, EGFR tyrosine kinase inhibitors erlotinib and gefitinib impair the regeneration of normal pulmonary epithelial cells [ 38 41 ] through the blockade of EGFR-dependent phosphorylation, and therefore this group of drugs is commonly incriminated as etiologies of interstitial lung disease, a lung-specific toxicity arising in NSCLC patients receiving these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Such signal fades away after normal organogenesis and tissue injury/repair to maintain homeostasis [ 37 ]. Unlike honokiol, EGFR tyrosine kinase inhibitors erlotinib and gefitinib impair the regeneration of normal pulmonary epithelial cells [ 38 41 ] through the blockade of EGFR-dependent phosphorylation, and therefore this group of drugs is commonly incriminated as etiologies of interstitial lung disease, a lung-specific toxicity arising in NSCLC patients receiving these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Development processes were found in the main process classification of T2DM, CML, and PCa. In cancer development process, TKIs also have been demonstrated to play a role through receptor tyrosine kinases (RTKs) signaling pathways . Recent studies on molecular therapies have indicated that TKIs may involve cell growth, migration, invasion, development, adhesion, proliferation, apoptosis, and angiogenesis via Nuclear factor‐kB (NF‐κB), Focal adhesion kinase (FAK), Janus kinase1/2 (JAK1/2), ETK, C‐Jun N‐terminal kinase (JNK), Mitogen activated kinase‐like protein (MAPK), Extracellular regulated MAP kinase (ERK), Phosphatidylinositol‐4,5‐bisphosphate 3‐kinase catalytic subunit alpha‐Serine/threonine kinase 1 (PI3K‐Akt), and other cancer‐related signaling pathways (Figure B) …”
Section: Discussionmentioning
confidence: 99%
“… 7 Gefitinib and erlotinib are the 2 most widely used receptor TKIs’ which selectively inhibit the EGFR tyrosine kinase domain. 8 In May of 2013, erlotinib was approved by Food and Drug administration as first line treatment of patients with metastatic NSCLC whose tumors had EGFR exon 19 deletions or exon 21 (L858R) substitution mutations. 2 Skin rash is one of the most common AE’s noted in the clinical trials, where its’ appearance has been associated with better overall survival.…”
Section: Discussionmentioning
confidence: 99%